The role of inoculum identity in drought stress mitigation by arbuscular mycorrhizal fungi in soybean - Grumberg, Betiana Clarisa; Urcelay, Roberto Carlos; Shroeder, María A.; Vargas Gil, Silvina; Luna, Celina Mercedes (2018)
It is well known that arbuscular mycorrhizal fungi (AMF) effects on plant growth largely depend on fungus identity. The objective of this study was to test whether three individual AMF isolates and their mixture mitigate drought stress (DS) differentially in soybean (Glycine max) genotype, predicting that under DS, the mixture of the AMF isolates would provide greater benefits to soybean plants than individual ones. In a greenhouse experiment, a drought-susceptible soybean genotype was inoculated with Septoglomus constrictum, Glomus sp., and Glomus aggregatum, known to be among the most abundant in agricultural and natural soils from central Argentina, and their mixture (Mx). Whereas under well-watered (WW) conditions, individual isolates and Mx treatment were similarly infective; under DS conditions, the Mx treatment showed lower rates of root colonization. Between WW and DS conditions, biomass was decreased in all treatments, although this effect was more marked in non-AM plants. Moreover, AMF strains improved water content and P and N concentrations. Under DS, the Mx treatment was unable to exceed the highest contents that were recorded by AMF isolates. However, under WW conditions, the Mx treatment showed a higher N content than individual isolates. Under both watering conditions, AM plants reduced oxidative damage evaluated as malondiadehyde and chlorophyll content and keep constant osmotic metabolites such as soluble sugars and proline content, without significant differences between AMF isolates and the Mx treatment. These results show that AMF play an important role in mitigating drought impacts on soybean, but that mixtures of AMF isolates did not perform as well as the best single strain inoculum, excluding complementarity effects and suggesting selection effect of AMF on DS alleviation in soybean.